Q69 (an E. faecalis-Infecting Bacteriophage) As a Biocontrol Agent for Reducing Tyramine in Dairy Products - Ladero, Victor; Gómez-Sordo, Carolina; Sánchez-Llana, Esther; del Rio, Beatriz; Redruello, Begoña; Fernández, María; Martín, M. Cruz; Alvarez, Miguel A. (Frontiers in Microbiology, 2016)
Biogenic amines (BAs) are low molecular weight nitrogenous compounds with biological activity, formed from amino acids by decarboxylation. BAs are naturally present in all living organisms playing essential roles. However, their accumulation in food through the metabolic activity of certain microorganisms constitutes a toxicological hazard. Among foods, cheeses accumulate some of the highest concentrations of BAs since they provide an ideal environment for their accumulation. Most of the methods proposed for reducing BAs in cheese, such as milk pasteurisation, have not only failed to completely solve the problem, they also affect non-BA producing lactic acid bacteria (LAB), i.e., the bacteria that participate in the development of the organoleptic characteristics of cheese. Novel technologies specifically targeted against BA producers are therefore needed to control BA accumulation. Bacteriophages have been proposed as agents for specifically controlling the presence of foodborne pathogens in food. Due to its specificity, they could be used as a biotechnological tool targeted to reduce the population of BA-producing bacteria. The present work reports the isolation, from cheese, and the characterisation of bacteriophage Q69, which infects specifically Enterococcus faecalis, the species mainly responsible of the accumulation of the BA tyramine in foods. Furthermore, its capacity to reduce the accumulation of tyramine in different conditions –including a model cheese- was proven. The obtained results open up the possibility of use bacteriophages to prevent BA accumulation in fermented foods.